Disjuncture as a Trope of Conjuncture in Sudeep Pakhrin’s Selected Poems - Lama, Kumari (Literary Studies, 2023)
Unremitting global flow of people have become the inherent characteristics of contemporary society. Since the concept of global village invaded each nook and corner of the world, thousands of people have been lining-up to enter into the global village from their local villages. They move leaving their ancestor’s places behind in the search of opportunities, better life, and to pursuing dreams. However, each such flow unknowingly creates a disjuncture within them. In this context, the paper argues that the specific disjunctive feeling itself becomes a means to connect them with their places and people. Mainly, they try to revisit their past, place and people through memory, which becomes instrumental for their reconnection. Concentrating on it, the paper critically examines the disjuncture as a trope of conjuncture in Sudeep Pakhrin’s selected poems. His poems, “Golden Street” and “Maavala” focus on the childhood memories that become strong thread to tie-up with his place and relatives in the verge of overpowering sense of disconnectedness. To critically analyze the isolated and vulnerable human condition in present society, I have employed Arjun Appadurai’s concept of global cultural flow and disjuncture as a theoretical backing.